Internationalization strategy of Shoes Closet to the United Kingdom - Capoulas, Maria Leonor Lopes (2012)
This Work Project analyzes the internationalization strategy of Shoes Closet, a Portuguese footwear SME, to the United Kingdom. It was based on fundamental support information provided by the company’s founder, on desk research and on market research. It tackles the domestic market, with a comprehensive internal and market scanning. It also analyses the British market, justifying the country choice and studying the competitive environment. Subsequently, this Work Project concludes that it is necessary to consider Portugal as a tactical market, implementing a deep change to foster the sustainable development of the company, to enter in the British market afterwards.